2019
DOI: 10.1242/bio.039917
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparative analyses of transcriptomes of cloned and in vivo fertilized porcine pre-implantation embryos

Abstract: Somatic cell nuclear transfer (SCNT) is the only method known to rapidly reprogram differentiated cells into totipotent embryos. Most cloned embryos become arrested before implantation and the details of the underlying molecular mechanism remain largely unknown. Dynamic regulation of the transcriptome is a key molecular mechanism driving early embryonic development. Here, we report comprehensive transcriptomic analysis of cloned embryos (from Laiwu and Duroc pigs) and in vivo fertilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Large-scale analyses of the embryonic transcriptomes have reported different MZT timing between in vivo -fertilized (IVO) embryos (four-cell stage) and SCNT embryos (eight-cell stage) ( Cao et al., 2014a ; He et al., 2019 ). Here, we investigated the RNA-seq profiles of two- to eight-cell IVO embryos (IVO2c, IVO4c, IVO8c), four- to eight-cell SCNT embryos (SCNT4c, SCNT8c), and the donor pig fetal fibroblasts (PFF) ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Large-scale analyses of the embryonic transcriptomes have reported different MZT timing between in vivo -fertilized (IVO) embryos (four-cell stage) and SCNT embryos (eight-cell stage) ( Cao et al., 2014a ; He et al., 2019 ). Here, we investigated the RNA-seq profiles of two- to eight-cell IVO embryos (IVO2c, IVO4c, IVO8c), four- to eight-cell SCNT embryos (SCNT4c, SCNT8c), and the donor pig fetal fibroblasts (PFF) ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the EGA-OFF genes, we surprisingly found that the deficient TDG expression could not be rescued by KDM4A + GSK126 treatment ( Figure 6 A). Notably, TDG is specifically transcribed during pig MZT ( He et al., 2019 ; Kong et al., 2020 ) and is barely detected at the MZT stage in mouse ( Deng et al., 2014 ; Liu et al., 2016 ), human ( Hendrickson et al., 2017 ; Yan et al., 2013 ), and cattle embryos ( Graf et al., 2014 ; Jiang et al., 2014 ) ( Figures 6 B and S4 C). TDG is a well-known enzyme for excising thymine, 5-hydroxymethyluracil (5hmU), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC), which are generated from either 5-methylcytosine (5mC) deamination by AICDA/APOBECs or 5mC hydroxylation by TET proteins ( Figure 6 C) ( Cortellino et al., 2011 ; Maiti and Drohat, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A fibroblast cell was inserted into the perivitelline space of enucleated oocytes with a smooth surface through the same slit [24]. After culture in PZM3 medium [26] at 39 • C for 1.5 h, the fusion of oocyte-donor cell complexes was performed via two successive DC pulses at 1.2 kV/cm for 30 µs [27].…”
Section: Scntmentioning
confidence: 99%